Investment Analysis of Integrated Milling-Sieving-Dewatering Machine for Grain Slurry Starch Production - Onyekachi, Egwuagu M.; Nduka, Nwankwojike B.; Osinachi, Onwuka S.; Princewil, Emeh C. (Kathmandu University Journal of Science, Engineering and Technology, 2021)
Economic viability of a continuous process milling-sieving-dewatering machine for grain slurry starch production was evaluated in this study using benefit-cost methodologies in order to encourage its wide acceptance/adoption. Benefit cost ratio, payback period, net present value and accounting rate of return constitute the economic parameters of the machine evaluated subject to prevailing economic indicators/market prices of materials in Abia State of Nigeria in 2020. Results revealed that the machine’s benefit-cost ratio, payback period, net present value and annual rate of return as 1.86 years, 1.75, 593,140.90 and 31.41% respectively. The investment’s benefit-cost ratio of 1.75 implies an inflow of 1.75 for every 1 spent The payback of 1.86 years is far less than 10 years useful life of the machine while its 31.41% accounting rate of return outweighed banks maximum fixed deposits return of 16% and prime lending rate of 29% in Nigeria. Thus, the machine is recommended for advancement of grain slurry food processing sector due to its positive capital recovery prospect.